Severity of chronic obstructive pulmonary disease and risk of one-year mortality after first-time implantation of implantable cardioverter defibrillator: a nationwide study. (3rd October 2022) - Alhakak, A; Mogensen, U M; Vinther, M; Risum, N; Jons, C; Jacobsen, P K; Torp-Pedersen, C; Fosbol, E L; Kober, L; Philbert, B T; Weeke, P E
Abstract: Background: Current guidelines, on implantable cardioverter defibrillator (ICD), recommend implantation in patients with an expected survival beyond one year. Information on risk of all-cause mortality among ICD recipients with chronic obstructive pulmonary disease (COPD) according to severity of COPD is lacking. Purpose: We examined the association between the severity of COPD and risk of all-cause mortality within one year after first-time ICD implantation. Methods: We identified patients ≥18 years old undergoing first-time ICD implantation with COPD using Danish nationwide registries (1 January 2000 to 31 December 2018). All patients were eligible for one-year follow-up. We used concomitant COPD-related pharmacotherapy six months prior to ICD implantation and COPD hospitalisations one year prior to ICD implantation to determine severity of COPD from mild to very severe according to Table 1. Multivariable Cox regression was used to assess risk of one-year all-cause mortality according to severity of COPD. Severity of COPD was adjusted for sex, age, year of implantation, primary prevention, type of ICD, history of atrial fibrillation, stroke, peripheral artery disease, diabetes, cancer, chronic renal disease, and dialysis. Results: The study population included 1, 536 patients with first-time ICD and COPD. The median age was 69.5 years [25th-75th percentile 63.5–74.3 years], and the majority of patients were males (79.4%). Of these, 896 (58.3%) received an ICD for primary prevention, and 485 (31.6%) had cardiac resynchronisation therapy device with defibrillator (CRT-D). In total, 1, 348 (87.8%) patients were diagnosed with heart failure. Patients were grouped according to severity of COPD from mild to very severe: Group 1 (N=666), Group 2 (N=72), Group 3 (N=149), Group 4 (N=445), and Group 5 (N=204). Overall, 154/1, 536 (10.0%) ICD recipients with COPD died within one year after first-time ICD implantation. No difference in sex and comorbidities was identified according to the five groups of COPD severity. However, ICD recipients with mild intermittent COPD (Group 1) were the youngest (68.3 years [61.8–73.0 years]). According to our multivariable cox regression in Figure 1, patients with very severe COPD (Group 5) were associated with increased risk of all-cause mortality within one year after first-time ICD implantation (adjusted hazard ratio [HR] 1.90 [95% confidence interval [CI]: 1.21–2.98]), compared with mild intermittent COPD (Group 1). The most common causes of death within one year after ICD implantation were attributed to cardiovascular diseases 95/154 (61.7%), respiratory diseases 15/154 (9.7%), and endocrine disorders 12/154 (7.8%). Conclusion: In this nationwide study, very severe chronic obstructive pulmonary disease was associated with increased risk of all-cause mortality within one year after first-time implantation of implantable cardioverter defibrillator. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Independent Research Fund Denmark